The Delima of Wisdom Tooth (Medical Forum Monthly, 2024)
Background: estimation of age from 17years to 23 is being in practice on the basis of eruption of 3rd molar tooth. However it is important to know whether this method is and will still be applicable in the present decade or in coming decades. Study Design: Cross Sectional Study. Place and Duration of Study: This study was conducted at Frontier Medical College, Abbattabad from May 2007 to April 2009. Materials and Methods: A cross sectional study is carried out in 400 students of FMC Abbottabad between 18 to 23 yrs of age to evaluate the status of eruption of 3rd molar tooth of both males and females. All informations were gathered on a performa especially designed for this purpose. Result: Record of 400 students was collected.6 performas were bias and rejected. Out of 394, 196 were males and 198 were females. All 4 erupted 3rd molar were seen in 90( 22.84%) students,3 erupted 3rd molar in 67(17%), 2 erupted 3rd molar in 63(15.98), 83(21.06) showed eruption of only one 3rd molar and last but not the least 91(23%) didn’t show eruption of 3rd molar at all. Conclusion: Result regarding 3rd molar tooth eruption shows that human beings of these decades are passing through evolutionary process of contracted jaw and resultant impaction of most of 3rd molars at the sight of eruption is the usual outcome. So we can predict that a time will come in coming few decades when forensic experts have to resort to some other factors to determine the age onwards from 17yrs rather than 3rd molar tooth eruption and development.